2016
DOI: 10.1016/j.apenergy.2016.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Energy saving potential of natural ventilation in China: The impact of ambient air pollution

Abstract: Natural ventilation (NV) is a key sustainable solution for reducing the energy use in buildings, improving thermal comfort, and maintaining a healthy indoor environment. However, the energy savings and environmental benefits are affected greatly by ambient air pollution in China. Here we estimate the NV potential of all major Chinese cities based on weather, ambient air quality, building configuration, and newly constructed square footage of office buildings in the year of 2015. In general, little NV potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 247 publications
(95 citation statements)
references
References 46 publications
0
94
0
1
Order By: Relevance
“…Cardinale et al, (2003) showed potentialities of natural ventilation in the reduction of cooling loads and energy consumptions need for the summer in Italy. Tong et al, (2017) estimated 7258 NV potential hours annually at ground level for Los Angeles. Naturally ventilated spaces depend on passive strategies for heating, cooling and the ventilation of the indoor environment.…”
Section: Introductionmentioning
confidence: 99%
“…Cardinale et al, (2003) showed potentialities of natural ventilation in the reduction of cooling loads and energy consumptions need for the summer in Italy. Tong et al, (2017) estimated 7258 NV potential hours annually at ground level for Los Angeles. Naturally ventilated spaces depend on passive strategies for heating, cooling and the ventilation of the indoor environment.…”
Section: Introductionmentioning
confidence: 99%
“…Current lines study the significant energy savings in most weather conditions [4], with respect to traditional mechanical exhaust systems [5], in different urban environments [6], occupancy profiles [7] and the ability to apply this strategy in building retrofits [8]. As for the influence on thermal comfort and indoor air quality, natural ventilation provides thermal control [9], free cooling [10] and contaminant removal benefits [11].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers worldwide have demonstrated that natural ventilation in buildings is an efficient passive strategy for thermal comfort and energy savings (Campaniço et al, 2014;Yu et al, 2015;Tong et al, 2016). According to the Brazilian bioclimatic zoning (ABNT, 2008), seven out of the eight zones are recommended to use natural ventilation for cooling.…”
Section: Natural Ventilation For Thermal Comfort and Energy Efficiencymentioning
confidence: 99%